EFISIENSI REPRODUKSI SAPI POTONG AKSEPTOR INSEMINASI BUATAN (IB) DI KECAMATAN TIKUNG, KABUPATEN LAMONGAN TAHUN 2015 DAN 2016 - Masruroh, Laili Salisa; Lokapirnasari, Widya Paramita; Restiadi, Tjuk Imam (Ovozoa: Journal of Animal Reproduction, 2019)
The aim of this study was to evaluate about reproductive efficiency of beef cattle by artificial insemination (AI) in Kecamatan Tikung Kabupaten Lamongan period 2015 and 2016. To determine reproductive efficiency by artificial insemination, data concerning the value of reproductive efficiency such as number of inseminated cattle, number of pregnancy, and the number of birth were collected. The raw data were processed to get the Service per Conception (S/C), Conception Rate (CR), Calving Rate (CvR). After processed, the obtained data was tabulated. The result showed that Service per Conception on 2015 was 1.28, on 2016 was 1.33. Conception Rate on 2015 was 79.45%, on 2016 was 7.94%. Calving Rate on 2015 was 81.08%, on 2016 was 78.54%. Conclution of reproduction efficiency is good. Based on data calculated of mean and standart deviation.